Knowledge transfer capability among technology-based firms in Malaysian technology parks - Mhd Sarif, Suhaimi; Ismail, Yusof (2010)
Knowledge transfer capability (KTC) is essential for technology-based firms (TBFs) to remain survive and competitive. KTC is determined by knowledge stocks (KS), social network (SN), and firm’s environment (FE). The KTC factors enable TBFs to be innovative with new products and services to the market. The study used personal interviews with 12 informants from TBFs located at several Malaysian technology parks. The results showed that Malaysian TBFs confirmed that their KTC is highly influenced by KS and SN, but not so much of FE. Future research suggests case study method for more details.